The impact of perceived CSR on corporate reputation and purchase intention - Bianchi, Enrique; Bruno, Juan Manuel; Sarabia-Sanchez, Francisco J (European Journal of Management and Business Economics (EJM&BE), 2019)
Purpose The purpose of this paper is to examine the influence of consumers' perceived corporate social responsibility (CSR). The aim is to provide insight into the effect of perceived CSR on purchase intention (short-term effect) and corporate reputation (long-term effect), whilst considering the role of brand image, satisfaction (affective and cognitive) and brand loyalty. Design/methodology/approach The sample comprised 429 consumers selected using non-probabilistic sampling with age and gender quotas. Confirmatory factor analysis was used to validate the measurement model. Structural equation modelling was used to validate the research hypotheses. Findings All direct and mediated influences in the model were significant, except for the effects of perceived CSR on affective satisfaction. Thus, the proposed causal chain is valuable to understand how perceptions of CSR influence purchase intention and perceived reputation. Research limitations/implications Perception is considered a dual phenomenon (cognitive and affective). It would be advisable to consider both dimensions in the future. The same is true of affective satisfaction. Originality/value Direct and mediated relationships that have previously been studied separately are considered together in a single model. This approach provides a better understanding of how perceived CSR influences purchase intention and reputation.